Women at the football matches. Czech Republic case study - Scholz, Petr; Vespalec, Tomáš (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The goal of this paper is to analyze the relationship between women visitors’ verbal and other expression and their violent behavior at selected football stadiums in Czech Republic. Primary data were collected by a questionnaire survey mainly at the Eden stadium in 2015/16 and 2016/17 seasons. A total of 120 respondents (aged 25.01 ± 10.20 years old) participated in this research, and all of the respondents were attending the matches in a stand of home team supporters. We found that expressions of demolishing the stadium and other riots are considered the most serious expression of violent behavior (supporters 100%, fans 84%, and spectators 64%). On the other hand, we observed that booing was considered the least serious problem (supporters 100%, spectators 64%, and fans 57%). In our opinion, the results are appropriate, but we expected higher values regarding racism display and comments like demolishing the stadium and other riots.